Experiences and Lessons Learned from COVID-19 Pandemic Management in South Korea and the V4 Countries - Gergő Túri; Attila Virág (Tropical Medicine and Infectious Disease, 2021)
In the first year and a half of the COVID-19 pandemic, South Korea suffered significantly less social and economic damage than the V4 countries (Czech Republic, Hungary, Poland, and Slovakia) despite less stringent restrictive measures. In order to explore the causes of the phenomenon, we examined the public health policies and pandemic management of South Korea and the V4 countries and the social and economic outcomes of the measures. We identified the key factors that contributed to successful public health policies and pandemic management in South Korea by reviewing the international literature. Based on the analysis results, South Korea successfully managed the COVID-19 pandemic thanks to the appropriate combination of non-pharmaceutical measures and its advanced public health system. An important lesson for the V4 countries is that successful pandemic management requires a well-functioning surveillance system, a comprehensive testing strategy, an innovative contact tracing system, transparent government communication, and a coordinated public health system. In addition, to develop pandemic management capabilities and capacities in the V4 countries, continuous training of public health human resources, support for knowledge exchange, encouragement of research on communicable disease management, and collaboration with for-profit and non-governmental organizations are recommended.